Evaluating edentulism and frailty in a group of elderly people treated at the dental clinic of Universidad San Martín de Porres in Lambayeque, Peru - Rubén Chumpitaz-Durand; Freddy Manayay-Llaguento; Daniel Córdova-Sotomayor (Universidad de Concepción., 2021)
Introduction: Dentistry should contribute to achieving healthy aging based on the identification of the well-being and oral health needs of the elderly. Objective: To evaluate the conditions of edentulism and frailty in a group of elderly people treated at the dental clinic of Universidad San Martín de Porres in Lambayeque, Peru, between the years 2016 and 2018. Material and Methods: An observational, descriptive, retrolective, and cross-sectional study was conducted. Two hundred and seven medical records that included an odontogram were randomly selected to identify cases of total or partial edentulism according to the Kennedy classification. The files were assessed with Fried's test to evaluate the conditions of frailty. The association between variables was estimated by means of a significance analysis using the Chi square test. Results: There was a statistically significant difference between edentulism in both jaws and conditions of frailty (p<0.05). An association of edentulism with physical inactivity and weakness was also demonstrated. Additionally, a statistically significant difference between degrees of edentulism was observed regarding poor diet (p<0.05). Conclusion: The absence of teeth in the elderly acts as a risk factor leading to negative changes in diet, weight, and physical activity. These changes may be associated with frailty, as masticatory insufficiency results in a poor diet and subsequent weakness.